Penggunaan Media Berbasis Teknologi Informasi dan Komunikasi (TIK) dalam Peningkatan Kemampuan Menulis Puisi Siswa Kelas III B SDN 005 Awang Long Samarinda - Ratna Khairunisa (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
Writing skills is one of the skills in language that needs to be developed and improved as a means of written communication. Writing should be done effectively and efficiently as writing is a productive and expressive activity. Improving writing skills needs to be done not only by using various approaches, strategies, and learning models, but also using appropriate and appropriate media. In this case, the teacher as a facilitator plays an important role to be able to choose the learning media in accordance with the learning ability of writing poetry. The method used in this research is Classroom Action Research (PTK) which is planned in 2 cycles. Each cycle is held in 3 meetings and carried out in accordance with the learning objectives to be achieved that is achieve learning mastery and by using media based on Information and Communication Technology (ICT). The type of this research is classroom action research and that will be the subject of research is the students of class III B SDN 005 Awang Long Samarinda with the number of students as many as 28 people. Data obtained through observation during the learning process takes place with the test at the end of the cycle, activity and motivation of students during the learning process takes place. The results of the data show the average value of student learning outcomes to the cycle. From the baseline value (initial condition value) obtained through the final test of observation done without the students is subjected to the action that is the average value of class 60, 53. From the average value of the initial condition increased in cycle I is 65.00. From cycle I to cycle II there is an increase in the activity and motivation of students, the value of learning results obtained from 65.00 to 79.10. The results showed that the use of media based on Information and Communication Technology (ICT) can improve the learning achievement of Bahasa Indonesia teaching materials to write poetry students of class III B SDN 005 Awang Long Samarinda.